2013
DOI: 10.4236/act.2013.21007
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Detector-Row CT Diagnosis of Adrenal Incidentaloma in Patients with Hepatocellular Carcinoma

Abstract: We investigate the diagnostic reliability of differentiating between lipid-poor adrenal adenomas and metastatic adrenal tumors originating from hepatocellular carcinoma (HCC) using a routine dynamic CT protocol for liver imaging. Eighteen metastatic adrenal tumors originating from HCC and 13 lipid-poor adrenal adenomas were identified. Dynamic CT data were analyzed for CT attenuation of adrenal lesions before and after contrast administration. When a cutoff of 36 HU was set for adrenal lesions at pre-contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…In our study, lipid-poor adenomas showed a lower unenhanced attenuation than nonadenomas (22 HU 6 6 vs 34 HU 6 7; P , .001), as in previous studies (5,(9)(10)(11)(12)(19)(20)(21)(22). Additionally, the absolute enhancement of adenomas was 1.5-fold higher than nonadenomas (P , .001), which is also corroborated by data from numerous studies wherein adenomas had higher (up to 2.2-fold) absolute enhancement compared with nonadenomas, mostly comprising metastases (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)14,16,22,29,30) (Table E4 [online]).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In our study, lipid-poor adenomas showed a lower unenhanced attenuation than nonadenomas (22 HU 6 6 vs 34 HU 6 7; P , .001), as in previous studies (5,(9)(10)(11)(12)(19)(20)(21)(22). Additionally, the absolute enhancement of adenomas was 1.5-fold higher than nonadenomas (P , .001), which is also corroborated by data from numerous studies wherein adenomas had higher (up to 2.2-fold) absolute enhancement compared with nonadenomas, mostly comprising metastases (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)14,16,22,29,30) (Table E4 [online]).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, adenomas showed an approximately 20% and 100% higher mean absolute enhancement and relative enhancement ratio, respectively, compared with hypervascular nonadenomas. Several previous studies have demonstrated equivalent or higher absolute enhancement in adenomas than in hypervascular nonadenomas (15,19,20,23,25,27,28,(31)(32)(33), while opposite results have also been observed in some investigations (A, B) an 84-year-old man with adrenal metastasis from hepatocellular carcinoma and (C, D) a 68-yearold man with lipid-poor adenoma. The lesions in both A and C had equivalent low unenhanced attenuation.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations